A clinical and experimental study of adult hereditary spherocytosis in the Chinese population. Issue 7 (5th March 2020) - Xue, Jun; He, Qing; Xie, Xiao‐Jing; Su, Ai‐Ling; Cao, Shi‐Bin
Abstract: Hereditary spherocytosis (HS) is often misdiagnosed due to lack of specific diagnostic methods. Our study summarized clinical characteristics and described the diagnostic workflow for mild and moderate HS in Chinese individuals, using data from 20 adults, 8 of whom presented a familial history for HS. We used scanning electron microscopy (SEM) to diagnose HS. We observed reduced eosin maleimide fluorescence activity (5.50 mean channel fluorescence (MCF) units) in the 10 cases of HS, which differed significantly when compared with 10 normal adults (15.50 units), iron deficiency anemia (15.50 MCF units), and megaloblastic anemia (12.00 MCF units) values ( P < .05). Next generation sequencing results revealed that 9 out of 10 patients were found to have mutations in the spectrin alpha chain ( SPTB ), anchor protein ( ANK1 ), and SLC4A1 genes. These mutations were not reported in the Human Gene Mutation Database (HGMD), 1000 human genome, ExAC, and dbSNP147 databases. Splenectomy proved to be beneficial in alleviating HS symptoms in 10 cases. It was found that for the diagnosis of HS, SEM and next generation gene sequencing method proved to be more ideal than red blood cell membrane protein analysis using sodium dodecyl sulfate polyacrylamide gel electrophoresis and western blotting.